EXPLORING THE ACADEMIC NEEDS OF RURAL UNIVERSITY STUDENTS IN PRE-INTERMEDIATE GRAMMAR COURSE - Ahyadi; Hustiana; Asdar (Universitas PGRI Palembang, 2024)
In order to assist lecturers in customising their teaching strategies and course materials for pre-intermediate grammar students living in rural locations, this study focuses on doing pre-lecture needs analysis. Using a quantitative method, 24 students enrolled in Universitas Sulawesi Barat's English Language Education programme for the academic year 2023–2024 were given closed-ended questions via a WhatsApp group. To find patterns in the gathered data, statistical analysis and purposeful sampling were applied. The results shed light on a variety of student characteristics, including age, mother tongue distribution, performance in the basic grammar course, ability to build simple English sentences, mastery of verb tense formulas, lexical proficiency, preferences for learning and assignments, and skill targets. The study draws attention to a variety of factors, including student skill objectives, favourite activities, assignment preferences, performance gaps, and vocabulary problems. Teachers and policymakers can improve the quality of English language instruction, particularly in grammar classes, and establish a supportive learning environment for students in Indonesia's rural areas by acknowledging and addressing the issues and preferences that have been identified. Furthermore, teachers around the world can use the needs analysis tool, the WhatsApp polling technique, and the pre-lecture activities as a source of inspiration and guidance to deliver engaging, balanced, and professional lectures that are customised to the needs of their students and meet graduate competency standards.